PENGARUH DISKON DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BUAH-BUAHAN IMPOR PADA TOKO NAYLA BUAH BENGKULU - Eriza, Nada; Bustami, Taufik (UM. Bengkulu, 2024)
The aim of the research is to determine the effect of discounts and product quality on purchasing decisions for imported fruit at the Nayla Buah Bengkulu shop. And to find out which factors most dominantly influence purchasing decisions. This research used quantitative methods on 150 respondents. The population used in this research was consumers of the Bengkulu Nayla Fruit Shop and sampling in this research used a non-probability sampling technique. Based on the results of multiple linear regression, the regression equation Y = 9.496 + 0.466 (X1) + 0.414 (X2) is obtained. The research results and hypothesis show that discounts and product quality have a partial or simultaneous positive effect on purchasing decisions. Keywords: Discounts, Product Quality and Purchasing Decisions.